(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Listening is a vital component of second language acquisition, yet listening tasks in many EFL/ESL textbooks often lack authenticity, featuring scripted dialogues that do not reflect real-life speech patterns. This article explores how language teachers can adapt textbook listening tasks using authentic audio materials. Drawing on insights from language pedagogy literature, teacher’s books from widely used textbook series, and reflective practices, the paper identifies practical methods and pedagogical principles for successfully integrating authentic materials. The discussion also examines challenges and solutions in the implementation process, emphasizing the importance of scaffolding, task design, and learner engagement.